FORMULASI DAN EVALUASI SEDIAAN MASKER GEL PEEL-OFF EKSTRAK ETANOL DAUN KELOR (Moringa oleifera L.) DENGAN BASIS Na-CMC DAN CARBOPOL - Aulia Debby Pelu; Jayanti Djarami; Irma Yanty Larajasi (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Moringa leaves (Moringa oleifera L.) contain flavonoid compounds, alkaloids, saponins, and tannins which are used as quality parameters of antioxidant preparations. Peel-off facial masks have several benefits, including being able to clean dirt on the face while removing dead skin cells, preventing skin damage caused by exposure to free radicals, such as acne and black spots, removing fine wrinkles due to premature aging, and moisturizing and nourishing the skin. The purpose of this study was to identify the chemical content of Moringa leaf (Moringa oleifera L.) and to formulate and evaluate the peel-off gel mask of the ethanol extract of Moringa leaf (Moringa oleifera L.) which was good and stable using a comparison of Na-CMC and Carbopol bases. . This research method is experimental which was carried out using Na-CMC base: Carbopol from three different formulations with a concentration ratio of F1 (3%: 0.1 %), F2 (4%: 1%), F3 (5%: 1.5 %), each formulation contains 3% Moringa leaf extract (Moringa oleifera L.). Evaluation of the peel-off gel mask preparation was carried out after 2 weeks of storage. The results showed an evaluation test of the peel-off gel mask preparation of Moringa leaf ethanol extract using Na-CMC and Carbopol bases on the homogeneity test of all homogeneous concentrations, the pH test showed that all concentrations of the preparation met the pH requirements, which ranged from 5-6, on the irritation test all the preparation did not cause redness and in the dry time test all preparations met the requirements, namely under 30 minutes. The conclusion of Moringa leaf ethanol extract using Na-CMC and Carbopol bases shows that it can be used as an alternative to cosmetics and can be used as a reference for use as natural cosmetics.